PlaneSpace MF1 : the "liberated company" experiment to build an innovative workplace - Kleinsmith, Niela, (SAGE Business Cases., 2018)
In 2015, Robert Dalman, head of manufacturing facility #1 (MF1) for PlaneSpace, a large European aerospace OEM, decided to transform his facility into an innovative workplace. In the prior 15 years, the facility had introduced major technological and process innovations, which had led to stagnant productivity and a disengaged and dissatisfied workforce. Having researched and studied organisational innovations, and brainstormed with his team, Dalman launched the "Liberated Company" experiment. This case describes the steps taken by the company to change its organisation and provides preliminary results. The case invites the reader to reflect on these actions and their short- and potential long-term outcomes, as well as on the impact of unions on organisational innovation.